2017
DOI: 10.1016/j.str.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The RNA-Binding Site of Poliovirus 3C Protein Doubles as a Phosphoinositide-Binding Domain

Abstract: SUMMARY Some viruses use phosphatidylinositol phosphate (PIP) to mark membranes used for genome replication or virion assembly. PIP-binding motifs of cellular proteins do not exist in viral proteins. Molecular-docking simulations revealed a putative site of PIP binding to poliovirus (PV) 3C protein that was validated using NMR spectroscopy. The PIP-binding site was located on a highly dynamic α-helix that also functions in RNA binding. Broad PIP-binding activity was observed in solution using a fluorescence po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…A fluorescence probe in the bilayer senses protein binding, causing fluorescence quenching for the proteins used to date. The system was validated using the Pleckstrin homology (PH) domain from phospholipase C δ1 that binds to PIP2 [ 47 ] and has now been validated for use with PI4P as well [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…A fluorescence probe in the bilayer senses protein binding, causing fluorescence quenching for the proteins used to date. The system was validated using the Pleckstrin homology (PH) domain from phospholipase C δ1 that binds to PIP2 [ 47 ] and has now been validated for use with PI4P as well [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, poliovirus (PV) and coxsackievirus B3 hijack the Golgi and TGN and recruit PI4K to the replication organelle to produce PI(4)P in situ [67,75,76]. The 3C replication protein binds directly to PI(4)P and PI(4)P is required for viral RNA synthesis [75,77]. PI(4)P is also required for sterol enrichment within the replication organelles of Rhinovirus and PV [78,79].…”
Section: Discussionmentioning
confidence: 99%
“…While the other functions that the HuNoV protease plays in the viral life cycle have yet to be fully elucidated, previous work has demonstrated that the HuNoV protease has RNA binding activity ( 32 ), as well as the ability to cleave cellular protease substrates ( 33 ). Work on the closely related poliovirus protease has also identified a phosphoinositide binding domain ( 34 ), but it remains to be determined whether the A105V mutation affects either of these or other as yet to be identified functions. It is noteworthy that the A105V mutation was not detected in isolation and was found only in combination with I109V.…”
Section: Discussionmentioning
confidence: 99%